Exploring the acceptance of mobile-assisted peer feedback in English speaking among Chinese EFL students - Weng, Jiayang; Noordin, Nooreen; Ahmad, Norhakimah Khaiessa (Society for Research and Knowledge Management, 2024)
Abstract. Grounded in the Technology Acceptance Model (TAM), this quasi-experimental study examined the use of Mobile-Assisted Peer Feedback (MAPF) tools via the Tencent Mini Programme among Chinese university EFL learners to enhance English speaking proficiency. A mixed-methods approach was employed, using descriptive statistics for questionnaire data and thematic analysis with NVivo for interview data. Sixty non-English major students (CEFR levels A2-B1) were selected through purposive sampling and assigned to three groups: one-way, dialogic, and visualised peer feedback. Results showed positive responses across all modes, with visualised feedback rated highest for usefulness, behavioural intention, and speaking improvement. The study highlights the need to consider technological, individual, and sociocultural factors in mobile-assisted feedback for language learning. Future research should explore long-term effects, application in diverse contexts, and further refinement of mobile-assisted feedback modes to enhance learner engagement. This study contributes to the research on MAPF in English speaking and offers practical insights for educational technology development. Keywords: Chinese EFL learners; English speaking proficiency; mobile-assisted peer feedback; Technology Acceptance Model